2015
DOI: 10.1097/tp.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Patient Barriers to Kidney Transplant Evaluation

Abstract: Background Some patients referred for kidney transplant evaluation fail to attend the visit. Our goal was to compare demographic, socioeconomic, and psychological factors between evaluation visit attendees and absentees. Methods A convenience sample of patients referred and scheduled for kidney transplant evaluation at a single center from November 2012 to December 2013 participated in a phone survey reporting socioeconomic, demographic and clinical characteristics; health literacy; and perceived knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 29 publications
0
70
0
4
Order By: Relevance
“…We found that lower HL levels were associated with an increased LOS during index hospitalization, such that patients with low HL levels (BHLS 3-8) spent an additional median of 1 day in the hospital compared with those with a high HL level (BHLS,15). Discharge from the hospital represents a complex transition in the lives of patients.…”
Section: Discussionmentioning
confidence: 89%
“…We found that lower HL levels were associated with an increased LOS during index hospitalization, such that patients with low HL levels (BHLS 3-8) spent an additional median of 1 day in the hospital compared with those with a high HL level (BHLS,15). Discharge from the hospital represents a complex transition in the lives of patients.…”
Section: Discussionmentioning
confidence: 89%
“…All others recruited from clinical environments without efforts to obtain a sample representative of a target CKD population. Two studies surveyed patients with CKD at transplant assessment clinics (37,41), whereas one excluded patients listed for transplant (19). Three studies reported offering a monetary gift to participants (45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%
“…Analyses were performed using the user-written commands metaprop and metareg in Stata 12 (StataCorp LP). Figure 1 shows the study selection process, which identified 433 unique studies, 15 of which met the inclusion criteria (23,24,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) with full agreement between the two reviewers. Table 1 summarizes the 15 new studies in addition to five studies included in the 2012 review (18)(19)(20)(21)47).…”
Section: Methodsmentioning
confidence: 99%
“…Transportation cost and access are more important barriers to referral and evaluation initiation compared with distance. Populations of patients with ESKD report transportation concerns as barriers to transplant access (6)(7)(8), and other studies among general populations have shown that transportation barriers (including lack of transportation in the form of car or mass transit and transportation cost) are important impediments to health care access in the United States (26)(27)(28). Furthermore, studies have shown that, although transportation is often more expensive for people living farther from clinics compared with those living closer, transportation is often reported as a concern equally among both rural and urban residents (28,29), suggesting that transportation barriers affect patients regardless of distance.…”
Section: Discussionmentioning
confidence: 99%